2007
DOI: 10.2223/jped.1610
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with duration of breastfeeding

Abstract: ResumoObjetivos: Determinar os índices de aleitamento materno exclusivo e complementado e identificar variáveis que interferem na prática da amamentação no município de Itaúna (MG). Resultados: A prevalência de aleitamento materno exclusivo no sexto mês foi de 5,3%, e de aleitamento materno aos 12 meses, 33,7%. A mediana de aleitamento materno exclusivo foi de 40 dias, e a mediana de aleitamento materno, 237 dias. A análise multivariada mostrou associação negativa (p < 0,05) entre o tempo de aleitamento matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
3
55

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 17 publications
4
43
3
55
Order By: Relevance
“…Some studies found that women who had less than 5 visits breast-fed their children for a shorter period, while those who had a greater number of visits also increased the length of the period of EBF [20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that women who had less than 5 visits breast-fed their children for a shorter period, while those who had a greater number of visits also increased the length of the period of EBF [20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…15 One factor which might have contributed to the results is the methodology used by initiative Hospital Amigo da Criança ("Friend of Children Hospital", in Portuguese) to increase breastfeeding rates, which is known to influence breastfeeding rates for term and preterm infants and which was being implemented at the neonatal ward at the time of this study. [16][17][18][19] One study limitation is that is was not designed, with breastfeeding as the primary outcome, despite the large sample size being sufficiently robust to explain such results.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to that observed in another Brazilian municipality close to the city of Bauru (odds ratio for EBF interruption associated with pacifier use = 2.7) 17 and is in accordance with several other Brazilian studies, which also demonstrated a strong association between the use of pacifier and early EBF cessation or interruption. 12,13,[19][20][21] A longitudinal study, carried out in the city of Porto Alegre, southern Brazil, revealed that almost two thirds of the children who used pacifiers were no longer on EBF after the second month of life; among the nonusers, the rate was 45%. 21 In another longitudinal study, the authors verified that 73% of pacifier users had discontinued EBF before three months of age; for nonusers, the rate was 58%.…”
Section: Worth Mentioning the Marked Drop In Ebf Observedmentioning
confidence: 99%
“…A possible explanation is that the use of pacifiers may hide maternal problems, such as anxiety and insecurity, which negatively affect breastfeeding. 12 A self-effect has also been attributed to the pacifiers, i.e., a causal relation between pacifier use and difficulties in breastfeeding: by reducing the number of breast feedings, there is a reduction in breast stimulation and milk secretion, increasing the chances of EBF interruption. 24 Another hypothesis to explain the effect of pacifier use as a risk factor for weaning is the mechanism called nipple confusion, which is already accepted as an explanation for the negative relationship between bottlefeeding and early weaning.…”
Section: Worth Mentioning the Marked Drop In Ebf Observedmentioning
confidence: 99%